The Educational Project of Abdelhamid Ben Badis:Between Reform and Renewal (مجلة إحالات, 2026)
This article—as the titlesuggests—addresses a topic related to the educationalfieldfrom theperspective of a genius man whowasahead of his time in thought, knowledge, and wisdom: Abdelhamid BenBadis. He left an enduringlegacy for Algeria and the Arab and Islamic world acrossvariousspheres of religious, political, social, historical, and educational life. Hisprimaryconcernwas the renaissance of theAlgerian people as a whole, and the youth in particular, lifting themfrom the depths of ignorance, illiteracy,and tyranny. He presented us with numerous reform projects, foremostamongthemhiseducationalproject. Inthisendeavor, hedevotedhisutmost efforts, balancing the aim of reform—to dismantle colonial-erarubble andcombat the colonial strategy of keeping the people ignorant—with the aim of renewal—to build acomprehensiveeducationalapproach capable of cultivatinghighlymotivatedcompetencies, rooted inauthenticbelonging, and sound in thinking and knowledge.